Methods of childbirth induction – a review of current knowledge - Kuźma, Jan; Łokczewska-Bojar, Aleksandra; Kuziemkowska, Daria; Łącka-Majcher, Anna; Tarsa, Grzegorz; Kępka, Przemysław; Sudelska, Katarzyna; Ben Rhaiem, Rami; Sawińska, Zuzanna; Skotalczyk, Magdalena (Journal of Education, Health and Sport, 2023)
Introduction: Pregnancy lasts 40 weeks from the first day of the last menstrual period, i. e. 280 days or 264 days from conception. It has been established that a child born between 37+0 and 41+6 weeks of gestation is a child born "on time". Unfortunately, in some cases it is necessary to terminate the pregnancy earlier, due to the condition of the pregnant woman, the baby or the approaching 42 weeks of pregnancy. Aim of the study: The aim of our study is to summarize available options for induction of childbirth. Particular attention was paid to available pharmacology and mechanical methods. The methods were compared in terms of effectiveness, possible complications and side effects. Materials and methods: A review of the current literature was made in the accessible PubMed and Google Scholar database, using the keywords: „birth induction”, „Cook’s catether”, „prostaglandin and oxitocine induction”, „amniotomy”, „membran stripping”. Conclusions: There are several ways to induce childbirth, which are used depending on current state of pregnacy. The availability of both pharmacotherapy and mechanical methods, allows the initiation of labor and termination of pregnancy by natural forces, in most cases avoiding the need to terminate the pregnancy by caesarean section.